Relationship between physical exercise and college students’ social adaptation: the chain mediating role of self-esteem and peer attachment - Zehui Zhou; Kelei Guo; Siqiang Guo; Lang Chen (Frontiers in Psychology)
ObjectivePhysical exercise is an important way for college students to keep healthy, and social adaptation is an important part of college students’ mental health. Therefore, this study explores strategies to enhance college students’ social adaptation from the perspective of physical exercise, examining the correlation between physical exercise and college students’ social adaptation, and delving into the roles of self-esteem and peer attachment in this relationship.MethodsA stratified cluster sampling method was used to collect data from 809 college students at Zhaoqing University (average age 19.88 ± 1.22, of whom 399 were male and 410 were female) using the physical exercise scale, college students’ social adaptation scale, self-esteem scale, and peer attachment scale. For data analysis, Pearson correlation analysis, structural equation modeling, and bias-corrected percentile bootstrap methods were sequentially performed.Results(1) Physical exercise was positively correlated with college students’ social adaptation (r = 0.58, p < 0.01), and the direct path between physical exercise and college students’ social adaptation was significant (β = 0.28, p < 0.01, CI[0.22, 0.33]); (2) Physical exercise was positively correlated with self-esteem (β = 0.56, p < 0.01, CI[0.50, 0.62]) and peer attachment (β = 0.18, p < 0.01, CI[0.11, 0.26]); self-esteem was positively correlated with peer attachment (β = 0.36, p < 0.01, CI[0.28, 0.43]) and college students’ social adaptation (β = 0.43, p < 0.01, CI[0.37, 0.49]); peer attachment was positively correlated with college students’ social adaptation (β = 0.18, p < 0.01, CI[0.12, 0.23]); (3) The relationship between physical exercise and social adaptation was not only mediated independently by self-esteem and peer attachment, but also indirectly by the same two factors in a chain reaction.ConclusionPhysical exercise can not only directly predict college students’ social adaptation, but also indirectly predict college students’ social adaptation through the independent mediation and chain mediation of self-esteem and peer attachment. It reveals that we should combine more important physical exercise with mental health education for students.